INTERNATIONAL MARKETING STRATEGY AND EXPORTING VENTURE PERFORMANCE OF EXPORTING BUSINESSES IN THAILAND - waranantakul, orawan; waranantakul, warawut (Asian Administration and Management Review, 2022)
The main research objective was to investigate the effect of international marketing strategy on export performance in Thai exporting businesses. The concept of resource-based view of the firm, structure-conduct-performance paradigm, and contingency theory were applied as theoretical underpinning. A five-point Likert scale questionnaire was used as an instrument for gathering data from 225 export businesses in Thailand and either managing director or marketing manager was assigned to be a key informant. The nine hypotheses were examined by using multiple regression analyses. Marketing activities coordination had a positive relationship with export performance, while concurrently specialized marketing capability was significantly related to all three dimensions of international marketing strategy. In aspect of moderating effect, market-focused learning positively moderated the relationship between entrepreneurial orientation and marketing activities coordination as well as the relationship between foreign market competitive intensity and marketing program adaptation. The managers should focus on coordinating value-chain activities across countries and leverage resources from different markets to gain access to location-specific advantages. Furthermore, top management need to provide supporting resources such as time and policies to improve international marketing employees’ capabilities and skills to satisfy both customer need and cost advantage.